IDENTIFIKASI FAKTOR PENTING YANG MEMPENGARUHI KEPUTUSAN MEMILIH BANK DALAM PERSPEKTIF NASABAH - Firman Agus Wahyudi (STKIP NU Kabupaten Tegal, 2021)
Identification of the Dominant Factors Contributing to the Decision to Choose a Bank from a Customer Perspective. The growth and competition in the Bank's financial institution sector has become increasingly competitive, so there is no single dominant bank among other competitors. Therefore, the Bank is required to be more competitive in carrying out business activities for business development. Knowledge of the factors influencing customers in choosing a bank is essential for the improvement and enhancement of banking products and services. This article presents a report on the factors that are important to influence customers in choosing a bank in conducting a review of similar articles. Based on the literature review from several studies, it can be identified the important factors that influence decisions in choosing information, competencies, brand image, costs and service quality.